Investigation of the Relationship between Care Burden and Self-Efficacy of Caregivers of Immigrant Individuals - Şeyma SOYANIT; İlknur AYDIN AVCI (Atatürk University, 2021)
Aim: This research is for the relationship between the burden of caregivers and self-efficacy to care for immigrant individuals. Methods: This descriptive study was conducted with the relatives of 302 migrant patients who care for migrant patients at Çorum Hitit University Erol Olçok Education and Research Hospital. The data were collected by caregiver and caregiver data collection form consisting of 48 questions and the Zarit Care Load Scale. A question about self-efficacy was asked in the data collection form. Analyses were performed with Shapiro-Wilks Test, Mann-Whitney U test, Kruskall Wallis test, Bonferroni correction by subgroup test when significance was determined, Spearman Rho correlation coefficient. Results: The average burden of caregivers for migrants was found to be 12.1±7.9. The fact that the immigrants who provide care are older, those with chronic diseases, those who have other responsibilities for care, those who need help, those who have difficulty in care, and those who do not feel enough to care, have a high burden of care. It seems that the age, gender and marital status of the migrant and care migrants affect the burden of care. Conclusion: As the self-efficacy of the caregivers increased, it was observed that the burden of providing care decreased.